MOTIVASI KOREA SELATAN MEMPROMOSIKAN BUDAYANYA MELALUI “TEKO NANG JAWA” DI INDONESIA PADA TAHUN 2019 - Maharani Octa Peddyaratri; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The focus of this research is to analyze the motivation of South Korea to promote its culture through the Teko Nang Jawa project in Indonesia. The spread of the Korean Wave in Indonesia encouraged South Korea to promote its culture in Indonesia, particularly in Java. In a new and unique way, the Embassy of the Republic of Korea conducted a bus tour around Java to promote its culture, especially to small towns in Java. Apart from promoting Korean culture, the “Teko Nang Jawa” event also held cultural exchanges in each destination city.This research uses a qualitative explanative method with a level of analysis of the nation-state. The theory used in this research is the theory of diplomacy in the perspective of pluralism. To analyze this research, the authors collected documents from books, journals, websites, dictionaries, as well as various information from the Embassy of the Republic of Korea to Indonesia.Based on the analysis conducted, it is concluded that this study shows that the "Teko Nang Jawa" project has been successfully done in various cities in Java Island. The motivation for South Korea to choose Indonesia to promote its culture through the Teko Nang Jawa project is because Korean culture has flourished in Indonesia, and South Korea wants to strengthen the cooperation between the two countries, especially in Java Island.  Key words: Motivation, Cultural Promotion, Korean Culture, Teko Nang Jawa